Professional Finnish Dancers' Experiences and Perceptions of Their Psychological Well-Being - Asikainen, Pauliina; Niemelä, Sanni (2023)
Dance is an extraordinary sport for not only having physical demands but also an artistic point of view with aesthetic, expressive and creative features. In professional dance field the high-pressure situations typical for dancers, such as auditioning for jobs, learning choreography or new skills fast, creating on the spot or with time pressure, taking care of physical fitness and performing, might occasionally require a lot of the psychological capacity as well as physical. The aim of this study consequently was to examine further on psychological well-being of professional dancers currently working in the industry in Finland. We interviewed six dancers with various demographic backgrounds, as well as lengths and descriptions of their careers in the dance field in Finland. Semi-structured interviews with open-ended questions were used in this research. Interviews were structured according to the research questions and included the areas of “Perceptions of well-being", “Factors challenging psychological well-being", “Perceived impact on well-being", “Factors supporting psychological well-being", “Experiences of coping techniques”, “Perceptions of psychological well-being’s current state in the Finnish dance field”, and “Dancers’ suggestions to support their well-being". Thematic analysis was used to analyze the data, through which the greatest commonalities amongst the participants’ answers were examined, which led to choosing the main themes and subcategories for each area of the interviews. Conclusion of the study was that there is great amount of stressors and pressure working in the dance field, and more careful attention should be paid in the psychological well-being of the professional dance field. There is more and more discussion around the topic but still not enough, and concrete measures should be taken in the practical level. As this research was executed in qualitative measures to examine the deeper individual perceptions and experiences of the psychological well-being of professional dancers, a quantitative study about the overall state of this topic would be extremely interesting. Also, a study conducted from the point of view of other professionals working in the dance field would be interesting and complete the picture of the phenomenon in question. Key words: Professional dancer, Psychological well-being, Coping